Aesthetics of style in Ba’i Hadba bin Al-Khashram Al-Adhari - مهنا بشرى (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research deals with studying some of the stylistic characteristics of Hadba bin Al-Khashram’s poetry through analyzing a poem of his that is rich in stylistic phenomena that require study, such as repetition at the level of its forms, such as deletion, introduction, and delay, as well as studying some of the repeated methods that produced semantic and aesthetic richness. We found the poet had deleted some elements and vocabulary in His poetry indicates the preservation of the music of the verse, and the meaning of the speech about it, and the repetition is also evident in indicating the confirmation of the emotional state full of sadness and depression on the one hand, and on the other hand the poet does not rest in peace with the pain and suffering that befell him, but rather there must be a space of hope in which he can take shade, and these phenomena We will study all of them in a practical aspect that was evident in his epistemology, in which he expressed emotional outbursts and spiritual outbursts that he translated into a poem worthy of study .